The Impact of Tax Avoidance on Firm Value with Profitability as a Moderating Variable : Case Study of Agricultural Companies Listed on the IDX 2020-2022 - Shofwatun Hasna; Khrisna Anggun Yuliana; Husin; M. Imam Suswandoyo (JOURNAL INTELEKTUAL, 2025)
Introduction/Main Objectives: To ultimately increase profits, the value of the Company, especially in the agricultural sector which has its own characteristics and challenges. Background Problems: The phenomenon of tax avoidance carried out by agricultural sector companies and its impact on company value, as well as the role of profitability as a moderating variable in the relationship. Novelty: Focus on the effect of tax avoidance on company value in the agricultural sector with an emphasis on the role of profitability as a moderating variable. Research Methods: Using a quantitative approach, the study population consists of agricultural sector companies listed on the IDX during the period 2020-2022 using statistical software (SPSS). Finding/Results: Tax avoidance can increase company value, profitability does not function as a reinforcement in the relationship, which indicates that other factors may be more influential in this context. Conclusion: This study concludes that tax avoidance has a significant influence on company value in the agricultural sector listed on the Indonesia Stock Exchange. However, profitability does not function as a moderating variable that strengthens the relationship between tax avoidance and company value.